CO 2 adsorption on polar surfaces of ZnO - Farias, Sergio A.S.; Longo, Elson [UNESP]; Gargano, R.; Martins, João B.L. (Springer Nature, 2012)
Physical and chemical adsorption of CO 2 on ZnO surfaces were studied by means of two different implementations of periodic density functional theory. Adsorption energies were computed and compared to values in the literature. In particular, it was found that the calculated equilibrium structure and internuclear distances are in agreement with previous work. CO 2 adsorption was analyzed by inspection of the density of states and electron localization function. Valence bands, band gap and final states of adsorbed CO 2 were investigated and the effect of atomic displacements analyzed. The partial density of states (PDOS) of chemical adsorption of CO 2 on the ZnO(0001) surface show that the p orbitals of CO 2 were mixed with the ZnO valence band state appearing at the top of the valence band and in regions of low-energy conduction band. [Figure not available: see fulltext.] © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: CO 2 adsorption; Electronic localization function; First principles; Plane wave; ZnO